Characterization of Dislocations in 4H-SiC Single Crystals at the Initial Growth Stage by Synchrotron X-ray Topography. (8th September 2020) - Ailihumaer, Tuerxun; Peng, Hongyu; Liu, Yafei; Raghothamachar, Balaji; Dudley, Michael
Abstract : This paper describes the investigation of dislocation behavior during the early stages of PVT-grown 6-inch 4H-SiC crystals by synchrotron monochromatic beam x-ray topography technique. Ray tracing simulation is applied to simulate the dislocation images. Our studies show that most TSDs/TMDs are replicated into the newly grown crystal while most TEDs are generated by either nucleation in pairs at the seed/crystal interface or by redirection of BPDs in the seed crystal. Most BPDs in the newly grown crystal are of screw type with 1/3 [112‾0], which is verified by comparison with the simulated images. TEDs with the same and opposite sign of Burgers vector are found to be deflected onto the same basal plane by the overgrowth of macro-steps and glide towards to the same or opposite directions respectively. TMDs deflected onto the basal plane get dissociated into a and c components, with the a segment undergoing glide to form V-shaped configurations.